Golgi Phosphoprotein 3 Promotes Colon Cancer Cell Metastasis Through STAT3 and Integrin α3 Pathways - Huang, Anpei; Wang, Ruizhi; Cui, Ji; Gao, Ying; Yin, Zheng; Chen, Lianzhou; He, Meifang; Li, Wen (Frontiers in Molecular Biosciences, 2022)
Background: Golgi phosphoprotein 3 (GOLPH3) overexpression was recently reported to be associated with a poor clinical outcome in patients with colorectal cancer (CRC). However, the underlying molecular mechanism through which GOLPH3 promotes CRC metastasis remains poorly understood. Methods: In vitro genetic ablation of GOLPH3 was performed using siRNA transfection, and a stably overexpressed GOLPH3 colon cancer cell line was constructed using the lentivirus system. Cell invasion and migration assays were conducted with or without Matrigel. Immunoblotting, qRT-PCR, immunofluorescence and immunohistochemistry were utilized to study the expression level of GOLPH3, ZEB1, integrin α3 and phosphorylation level of STAT3, AKT/mTOR and Raf/MEK/ERK pathways. Co-immunoprecipitation was used to investigate the interaction between GOLPH3 and p-STAT3(Tyr705) or total STAT3. Results: Overexpression of GOLPH3 was found in CRC tissues and colon cancer cell lines. Knockdown of GOLPH3 using siRNAs significantly suppressed the invasion and migration of HCT116 and HCT8 cells. In contrast, the overexpression of GOLPH3 promoted the migratory and invasive ability of colon cancer cells. The phosphorylation level of STAT3 as well as the protein and mRNA levels of ZEB1 and integrin α3, were significantly decreased after GOLPH3 knockdown. Moreover, Integrin α3 expression was correlated with GOLPH3 expression in CRC tissues. Co-immunoprecipitation assay revealed that GOLPH3 interacted with pSTAT3(Tyr705) and total STAT3. Our further experiments suggested that GOLPH3 facilitated IL-6 induced STAT3 activation and subsequently induced transcription of Integrin α3 and ZEB1, which promoted the metastasis and progression of CRC. Conclusion: Our current work demonstrates that GOLPH3 facilitates STAT3 activation and regulates the expression of EMT transcription factor ZEB1 and Integrin α3 in colon cancer cells. These findings indicate that GOLPH3 plays a critical role in CRC metastasis and might be a new therapeutic target for CRC treatment.